Peran Celebrity Endorser Terhadap Perilaku Konsumen Saat Pembelian Online Pada Platform E-Commerce - Ridha Amallia Riadi; Idfi Setyaningrum; Cynthia Yohanna Kartikasari (Jurnal E-Bis, 2023)
Due to the fierce competition in e-commerce throughout the digital economy era, business participants must develop strategies to improve competitiveness for long-term sustainability and growth. The employment of celebrity endorsers, which is predicted to impact customer behavior during online shopping, is one of the most effective tactics for increasing consumer interest in purchasing products. The qualitative-descriptive research method was used, including secondary data. According to the report, numerous businesses have already begun selling online but have yet to fully realize the benefits of e-commerce. Interestingly, when it comes to customer behavior, internet purchases have a higher percentage of consumer interest than physical sales. Celebrity endorsements have a tremendous impact on customer behavior when purchasing things on e-commerce platforms